Sharia Pharmacy: Ethical Perspectives on Generic Drug Use in Contemporary Medical Practice - Meia Yevi Setyawati; Nisa Rahmadila Rizqi; Arham Agusto; Syifa Al Haninah; Aninditya Ayu Oktaviani; Abdulrohim E-sor; Hamzah Al-Haqqoni (Demak Universal Journal of Islam and Sharia, 2025)
Objective:  To analyze the relationship between modern pharmaceutical practices and Sharia principles, focusing on the halal compliance of generic drugs, and to explore how these principles enhance accessibility, fairness, and ethical integrity in healthcare. Theoretical framework: This study is grounded in Sharia pharmacy principles, emphasizing Islamic ethics (halal, fairness, and social responsibility) as well as the balance of benefits and risks in modern pharmaceutical practices. Literature review: The review includes studies on the development and use of generic drugs in Indonesia, the integration of halal certification in pharmaceutical production, and the ethical considerations in Sharia-compliant healthcare systems. Methods: A qualitative approach analyzing regulations, halal certification standards, and ethical guidelines in Sharia pharmacy, combined with a conceptual analysis of the alignment between generic drug practices and Islamic values. Results: The findings highlight that generic drugs, when produced according to halal principles, provide both affordability and ethical assurance. The study confirms the importance of halal certification to ensure the suitability of pharmaceutical products for the Muslim community and the alignment of modern practices with Sharia ethics. Implications: The study suggests the need for stronger collaboration between pharmaceutical companies, halal certification bodies, and healthcare professionals to ensure the integrity and accessibility of Sharia-compliant medicines in Indonesia. Novelty: This research uniquely bridges the gap between modern pharmaceutical practices and Sharia ethics, offering a comprehensive perspective on how generic drugs can fulfill both economic and religious requirements in the healthcare system.